Do ESG disclosure scores drive financial success? A dynamic panel analysis of Thai firms - Abubakr, Ayman Abdalla Mohammed; Mohammed, Ali Alhag Ali; Sahal, Mastora Sahal Gomaa; ALI, Mohamed Ali; Hussin, Hiba Awad Alla Ali (Asian Economic and Financial Review, 2025)
This study aims to explore the relationship between environmental, social, and governance (ESG) disclosure scores and financial performance among publicly listed firms in Thailand from 2014 to 2023. The study uses a methodology by designing a system GMM and difference GMM estimations. The findings provide robust insights into how ESG disclosure scores influence firm profitability and market valuation. The results reveal that environmental disclosure scores negatively affect accounting-based performance measures (ROA and ROE) but positively influence market valuation (Tobin’s Q). The social disclosure score consistently enhances ROA, ROE, and Tobin’s Q. The governance disclosure score presents mixed results, with system GMM showing a negative impact on all performance measures, while difference GMM indicates a positive effect on ROA and ROE but a negative influence on Tobin’s Q. Firm-specific characteristics also play a significant role, as higher leverage weakens financial performance, and liquidity management has varying effects. The practical implications of the study, through its contribution to the literature, are to provide empirical evidence on environmental, social, and governance disclosures in the context of emerging markets. Finally, the study recommends the need for a well-structured policy framework that ensures that environmental, social, and governance initiatives lead to long-term financial stability, investor confidence, and sustainable economic development.